"The Persistent Monster": Coronavirus Nightmares and Capitalist Crisis in New York City - Palencia Frener, Sergio (Anthropology of consciousness, 2026)
In March-May 2020, New York City's college students suffered sudden lockdown due to the COVID-19 pandemic and a mandatory transition from in-person classes to virtual meetings. Unexpectedly, my introductory course to anthropology transformed into a collective space to share experiences of the city in times of crisis. This article examines in-class conversations on nightmares and the variety of contemporary hauntological experiences in the context of a global pandemic. Through students' conversations and written reports, personal journal entries, and photos, this article discusses COVID-19-related nightmares that depict phantasmagoric spaces, globalized dream narratives, bad omens, media oneiric compositions, and struggles against neighborhood monsters. I argue that the COVID-19 pandemic magnified experiences of fear, isolation, and loneliness in everyday life under capitalism. The article presents oneiric phenomena characterized by a global exchange of COVID-19-related dreams and nightmares. Smartphones allowed international students to exchange dream interpretations with their kinship networks in other continents. While nightmares show the increasing penetration of capitalist relationships and media in students' dreams, this article contends that dream narratives contain anti-capitalist images as well, a subterranean "specter" that potentially questions "capitalist realism".